Eating disorder risks and awareness among female elite cyclists: an anonymous survey - Koppenburg, C.; Saxer, F.; Vach, W.; Lüchtenberg, D.; Goesele, A. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Eating disorders (EDs) are an increasingly recognized concern in professional sports. Previous studies suggests that both female gender and endurance sports put athletes at risk. Female elite cyclists are hence of specific interest. The present study aimed at evaluating the distribution of the individual risk of ED in this group. Further the association between individual risk and both the awareness for the topic ED and the deviation from "normal" weight was depicted.